The Carboxyl Terminus of RNA Helicase A Contains a Bidirectional Nuclear Transport Domain - Tang, Hengli (American Society for Microbiology, 1999)
Human RNA helicase A was recently identified to be a shuttle protein which interacts with the constitutive transport element (CTE) of type D retroviruses. Here we show that a domain of 110 amino acids at the carboxyl terminus of helicase A is both necessary and sufficient for nuclear localization as well as rapid nuclear export of glutathione S-transferase fusion proteins. The import and export activities of this domain overlap but are separable by point mutations. This bidirectional nuclear transport domain (NTD) has no obvious sequence homology to previously identified nuclear import or export signals. However, the Ran-dependent nuclear import of NTD was efficiently competed by excess amounts of the nuclear localization signal (NLS) peptide from simian virus 40 large T antigen, suggesting that import is mediated by the classical NLS pathway. The nuclear export pathway accessed by NTD is insensitive to leptomycin B and thus is distinct from the leucine-rich nuclear export signal pathway mediated by CRM1.